2011 International Conference on Advanced Power System Automation and Protection 2011
DOI: 10.1109/apap.2011.6180429
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of protection performance in UHV transmission line with multi series capacitors compensation

Abstract: Series capacitor can enhance transmission capability of power grid and optimize the power flowed to improve the transient stability of power systems. However, they change the magnitudes and the directions of fault voltages and currents in series compensated networks and impact the protection performances. This paper analyses the fault electric quantity characteristics and discusses the operation behaviors of protection relays on transmission lines with multi series capacitors. Some suggestions for improving th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…1)When the transmission line capacity decreases, it is equivalent to reduce of the cross section and increase the impedance of the be ensured [24]. Therefore, the increase of line impedance will further aggravate the voltage drop in the situation of forward power flow, and a similar phenomenon can be conducted in the situation of reverse power flow.…”
Section: Influence Of Transmission Line Capacity On Node Voltagementioning
confidence: 99%
“…1)When the transmission line capacity decreases, it is equivalent to reduce of the cross section and increase the impedance of the be ensured [24]. Therefore, the increase of line impedance will further aggravate the voltage drop in the situation of forward power flow, and a similar phenomenon can be conducted in the situation of reverse power flow.…”
Section: Influence Of Transmission Line Capacity On Node Voltagementioning
confidence: 99%
“…However, this method is mainly focused on the suppression of the power frequency overvoltage, therefore, it has no obvious effect on the oscillating overvoltage of the transmission process. To this end, the series compensation capacitor method is therefore presented in [6][7], and their simulation results showed that the switching overvoltage can be suppressed to some extent. But the method still cannot meet the overvoltage reference standard of the ultrahigh voltage operating and hence, it can only be used as the auxiliary method.…”
Section: Introductionmentioning
confidence: 99%